INTEGRATION OF PALLIATIVE CARE INTO UNDERGRADUATE HEALTH AND SOCIAL CARE CURRICULA IN THE REPUBLIC OF SERBIA. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Downing, Julia; Haraldsdottir, Erna; Milicevic, Natasa; Bosjnak, Vesna; Firth, Pam; Lukic, Nina; Baskott, Jo
Abstract : Background: Palliative care remains a new discipline within Serbia, thus there is a need for a comprehensive programme of continuing education and formal higher education for palliative care (PC). Prior to 2011, there was no formal palliative care training incorporated into the undergraduate curriculum for health and social care professionals. Therefore the introduction of palliative care into the curriculum for doctors, nurses and social workers was a key component of the development of palliative care. Aim: The aim was to integrate pc into the undergraduate curricula of medical, higher nursing and social work curriculum in Serbia. Methods: A team of national and international experts led the process. For each discipline, contact was made with the appropriate Deans, meetings held with representatives from the different faculties, and a curriculum development process established. Existing curricula were reviewed, where they existed e.g. for the medical schools and curricula drafted based on international guidelines/experience. Results: Comprehensive training materials have been developed, including facilitators guides, presentations and student handbooks, as there is no comprehensive Serbian PC book. The curriculum has been integrated into the undergraduate medical course in all five medical schools in Serbia i.e. the Universities of Belgrade, Novi Sad, Kragujevac, Nis, and the Military Medical Academy. The process of acceptance into the higher nursing schools is ongoing but it is anticipated that at least half of the schools will integrate palliative care as a mandatory course. For social workers, palliative care will be taught within the curriculum for the first time from October 2013. Conclusion: Integration of pc into the undergraduate curriculum for health and social care professionals is vital in the development of pc. Working in collaboration with the different faculties is key to integration, along with development of comprehensive training materials in accordance with European and International standards.